Analisis Informasi Publik di Kepolisian Sektor Pademangan - Gracia Irena Saputri; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This research discusses public information in the Pademangan Sector Police. Public information is an important part of public administration. Public information is all information that is publicly available and can be accessed by the public freely. This information may include government data, public reports, legal documents, or other relevant content. The importance of public information in society is to encourage transparency, accountability and citizen participation in the democratization process. However, effective management and access to public information also raises issues related to privacy, security and ethics. The use of public information is also to provide open and transparent access to information produced or managed by the government or public institutions to the general public. This aims to enable the public to understand, monitor and participate in government and decision-making processes. Public information enables the public to have sufficient knowledge to evaluate government performance, understand public policy, and play an active role in community development and maintaining government accountability. Therefore, it is important for the government and other agencies, including the police, that provide public information to consider the interests of the community and maintain the basic principles of fair and just public information.